2013
DOI: 10.1111/bjd.12426
|View full text |Cite
|
Sign up to set email alerts
|

E- to N-cadherin switch in melanoma is associated with decreased expression of phosphatase and tensin homolog and cancer progression

Abstract: Cadherin switch and reduced/absent PTEN expression are associated in melanoma, and both factors may play important roles in the progression of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 34 publications
2
59
1
1
Order By: Relevance
“…These modifications may promote carcinoma cells to acquire invasion ability, which constitutes a critical step in tumor malignancy and metastasis [33, 34]. The E- to N-cadherin switch has been related to increased cell invasion, tumor progression and metastasis in melanoma and other carcinomas [30, 3537]. …”
Section: Discussionmentioning
confidence: 99%
“…These modifications may promote carcinoma cells to acquire invasion ability, which constitutes a critical step in tumor malignancy and metastasis [33, 34]. The E- to N-cadherin switch has been related to increased cell invasion, tumor progression and metastasis in melanoma and other carcinomas [30, 3537]. …”
Section: Discussionmentioning
confidence: 99%
“…While Mikhail et al 60 found that altered PTEN expression was correlated with tumour ulceration, no association has been shown with either disease-free60 61 or overall60–62 survival. We have recently demonstrated a strong association between reduced PTEN IHC expression and ulceration, Breslow thickness and tumour stage, as well as with a poor overall relapse-free survival in univariate analysis 36. This suggests that a reduction in PTEN expression plays an important role in melanoma genesis and in the development of melanoma metastases.…”
Section: Discussionmentioning
confidence: 92%
“…The patient cohort and tissue microarray (TMA) were as described previously 36. In brief, the TMA contained sample cores from 355 primary melanomas and 37 benign and non-dysplastic naevi (19 dermal and 18 compound naevi).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will focus specifically on E-cadherin and N-cadherin’s relevance to both the NC and cancer. In many cell types including the NC, EMT has long been associated with a cadherin switch that involves decreased E-cadherin and increased N-cadherin (Araki et al, 2011; Gravdal et al, 2007; Lade-Keller et al, 2013; Scarpa et al, 2015; Wheelock et al, 2008), although the importance of this particular cadherin switch remains a point of significant debate due to the perdurance of E-cadherin post-EMT in some cases (Dady et al, 2012; Dady and Duband, 2017; Huang et al, 2016). During EMT in cancer, there is usually a similar transition entailing a downregulation of E-cadherin at cell-cell junctions and an upregulation of N-cadherin (Kuphal and Bosserhoff, 2006; Thiery, 2002), but as with the NC, there may be exceptions to this behavior (Yan et al, 2016).…”
Section: Delamination and Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%